Linking Smart Governance to Public Innovation: The Mediating Role of Digital Citizen Participation and the Moderating Influence of Trust and Readiness in Brazil - Anderson Catapan (Journal of Advanced Research in Social Sciences and Humanities, 2026)
Aim: This study investigates the impact of smart governance on policy innovation and public service performance in Brazil, while examining the mediating role of digital citizen participation and the moderating effects of digital trust and technological readiness. It aims to explain how digital governance mechanisms translate into meaningful public sector outcomes in a rapidly developing digital ecosystem.Methodology: A quantitative, cross-sectional research design was employed, and data were collected from 275 government officials and digitally active citizens from Brasília, São Paulo, and Rio de Janeiro using a structured questionnaire. Stratified random sampling was used to ensure regional representation. The data were analyzed using SmartPLS to test direct, mediating, and moderating relationships.Findings: The results revealed that smart governance significantly enhances both policy innovation and public service performance. Digital citizen participation was confirmed as a strong mediator, while digital trust and technological readiness significantly strengthened the impact of smart governance and digital participation on outcomes.Originality/Implications: This study advances digital governance theory by integrating psychological and infrastructural enablers into a unified model. It offers practical guidance for policymakers by demonstrating that effective digital transformation requires not only smart governance systems but also citizen trust, active participation, and technological preparedness.